Epistemiology of the South - “Navigating and Traversing the Proverbial Avalanche Post Phd in the 21st Century – A Narrartive Reflection” - Ntsobi, Mfanelo, Patrick (My University, 2022)
Knowledge can be transmitted, facilitated, developed, and produced in a variety of ways through education. As a matter of fact, universities, in particular, are defined in terms of knowledge generation. We shouldn't be surprised, then, that discussions about decolonizing (Western) education have expanded to encompass provincializing (Western) epistemology, given the close ties between education and educational institutions and epistemology. This presents a danger as epistemological pathways inform thinking partners and behavioural dynamics of societies. Deconstructive debate that seeks to discuss educational decoloniality from the Global South cannot articulate that with exclusion of southern epistemological position towards reality with the lens of its inhabitants. This is what confronts the post-doctoral scholar of the Global Centre for Academic Research and South Valley University, as independent entities within the Global South. This narrative reflection provides a baseline for a cogent discourse in favour of deconstruction of southern epistemological trajectory in education and social perspectives.
Keywords: Decoloniality; Doctoral education; Social Discourse; Southern Epistemology